Multiply:
1. (5x + 3) by (7x + 2)
2. (2x + 8) by (x – 3)
3. (3x2 + y2) by (2x2 + 3y2)
Answers
Answered by
1
Answer:
1)35x²+31x+6
2)2x²+2x-24
3)3y⁴+22y²+24
Answered by
0
Answer:
1=35x2+10x+2
2=2x+24-2x2
3=6x4+6x4y4+3y4
Step-by-step explanation:
1. 5x(7x+2) + 3(7x+2)
=35x2+10x+21x+2
=35x2+10x+2
2. 2x(x-3) + 8(x-3)
= 2x2- 6x+ 8x + 24
=8x - 6x + 24 -2x2
= 2x+ 24 -2x2
3. 3x2(2x2+3y2)+ y2( 2x2+3y2)
=6x4+3x2y2+ 2x2y2+3y4
=6x4+ 6x4y4+3y4
plzz follow me if helpful n thnk my ans
Similar questions
Math,
4 months ago
Social Sciences,
4 months ago
Hindi,
8 months ago
Biology,
1 year ago
English,
1 year ago